ASAS FILOSOFIS DALAM PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM - Muh Rezky Ramadhan Syamsuddin; Tasman Hamami (Raudhah - Proud To Be Professional, 2023)
Abstract, Curriculum development has a strong philosophical foundation so that goals can develop clearly and precisely. So that philosophical principles and other principles are needed in the development of an Islamic religious education curriculum. This writing aims to find out the philosophical principles in the development of the Islamic religious education curriculum. This writing method uses literature review and manages data with descriptive analysis in an objective and systematic way. The results of this research are that the philosophical principles in curriculum development have philosophical goals and that national education is used as the basis for formulating institutional goals in producing educational institution curricula. As for the philosophical schools in the development of the Islamic religious education curriculum, these principles include perennialism, essentialism, existentialism, progressivism, reconstructionism. The conclusion from this study is that the philosophical principles in the development of the Islamic religious education curriculum contribute to the development of the curriculum, both theoretically and practically.